Towards explainable artificial intelligence in the banking sector - Jew, Clarissa Bella (Nanyang Technological University, 2024)
This research addresses the imperative need for Explainable AI (XAI) tools tailored to the banking industry, where widespread adoption of AI has led to escalating demands for explainable and transparent models. The methodology involves the implementation of a user-centric system using the DASH framework and introduces a novel approach of integrating two XAI techniques, SP-LIME and SHAP, with the aim of capitalizing on the strengths of each tool.